Notes on Bulbophyllum (Dendrobiinae; Epidendroideae; Orchidaceae): Two new species and the dilemmas of species discovery via illegal trade - Jaap J. Vermeulen (2018)
© 2014 Magnolia Press. Bulbophyllum anodon (section Brachystachyae) and B. dasystachys (section Hirtula) are described. Bulbophyllum cylindraceum is newly recorded for Thailand. Bulbophyllum dhaninivatii and B. tripaleum (section Lemniscatae) are synonymized. Notably, all specimens discussed in this paper first came to scientific attention via illegal trade. Although many new species have emerged as a result of commercial ventures, it is alarming that contemporary orchidological discovery in some regions continues to be driven by trade. We briefly discuss the tensions associated with describing new species discovered via illegal trade, including some of the associated scientific and moral implications.